Evaluating the potential of chitin extracted from shrimp shell wastes as support material of gold nanoclusters (AuNCs) for catalysis - Zakaria, Nabila Azirah; Nasaruddin, Ricca Rahman; Wan Nawawi, Wan Mohd Fazli (IOP Publishing, 2022)
Thiolate-protected gold nanoclusters (AuNCs) have been intensively studied due to their appealing physicochemical properties that can be used in various applications, especially catalysis. However, thiolate-protected AuNCs in a free suspension form, tend to aggregate during catalytic reaction due to the high surface reactivity of its ultrasmall size, hence, reducing the rate of their catalytic reaction. Their recovery and reusability are also difficult. Therefore, several support materials have been studied to immobilize the thiolate-protected AuNCs for a better recovery, reusability and stability in solution and during a catalytic reaction. Herein, chitin extracted from shrimp shell waste was used as support material for the immobilization of the AuNCs protected by p-mercaptobenzoic acid ligands, using the deposition-precipitation method. The free chitin and chitin immobilized with thiolate-protected AuNCs (abbreviated as AuNCs/Chitin) were characterized using FTIR. The catalytic properties of the AuNCs/Chitin were then evaluated in the hydrogenation of 4-nitrophenol in solution as the model reaction. It was found that the chitin extracted from SSW has a good potential to be support materials of thiolate-protected AuNCs because of the shorter reaction time it took (12 minutes) as compared to the reaction without catalyst (60 minutes) and it can be recovered and reused twice.